Ikhwan Muslimin Thoughts on Islamic State - Ahmad Dzulfahmi Muhamad (Proceedings of AICS - Social Sciences, 2017)
This study looks at the political thoughts of the Ikhwan Muslimin (IM) leader on the Islamic state. The focus of this study is to examine the political thoughts of every IM leader in bringing this movement into the Egyptian political scene. The objective of this study is to examine the changes in the political thinking of each IM leader. This study uses qualitative research methods based on primary and secondary sources and analyzed using historical approaches. The primary source data used is the British Record such as official reports, letters, memorandums and telegrams obtained at The National Archives London. In addition, secondary sources used are articles, journals, books, papers and theses to support the results of the study. The findings show that there are some changes in the aspect of IM political thinking among their leaders of this movement. This change of IM thought is due to the political pressure faced by IM from Egyptian Ruler who see this movement as a threat to their power